Sitologi Berbasis Konvensional dibandingkan dengan Cairan sebagai Skrining Kanker Servik : Sebuah Sistematik Review - Oki Mashera Ratman; Chandra Nurreza Fauzi; Nurlina Juniar (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
Worldwide, there are 2.784 million women aged 15 years and over who are at risk of cervical cancer, and about 527,624 new cases of cervical cancer are diagnosed each year. Cervical cancer ranks as the fourth leading cause of cancer in women worldwide, and is the second most common cancer in women between the ages of 15 and 44. Cervical cancer can have devastating effects with very high costs, socially, and economically, affecting women in their productive years. Screening with routine cytology, using Papanicolaou (Pap) staining, has a major impact on the incidence of cervical cancer in many countries. In developed countries, but not in any developing country although its use is widespread. The use of conventional cytology as the primary test method has been replaced by the use of liquid-based cytology in many countries that have organized cervical cancer screening programs, such as the United Kingdom, the Netherlands, and Denmark. The main advantages of using liquid-based cytology instead of primary conventional cytology are that it facilitates reflex testing (i.e., residual material can be tested for the presence of human papilloma virus if borderline/slightly dicariotic smears are present) and reduces the number of slides of unsatisfactory quality. This literature review study aims to further examine how conventional cytology compares to liquid-based cytology as a method used in conducting cervical cancer screening. The journal in this review literature uses 3 databases including Google Scholar, PubMed, and Science Direct using the keywords "liquid based cytology", "conventional cytology" and "cervical cancer screening". Literature searches are adjusted based on inclusion and exclusion criteria. The search results were obtained by 10 international journals. Results show that both conventional and liquid-based cytology are effective methods for cervical cancer screening. Although liquid-based cytology may have some advantages over conventional cytology, both methods have proven effective for detecting cervical pathologies.Worldwide, there are 2.784 million women aged 15 years and over who are at risk of cervical cancer, and about 527,624 new cases of cervical cancer are diagnosed each year. Cervical cancer ranks as the fourth leading cause of cancer in women worldwide, and is the second most common cancer in women between the ages of 15 and 44. Cervical cancer can have devastating effects with very high costs, socially, and economically, affecting women in their productive years. Screening with routine cytology, using Papanicolaou (Pap) staining, has a major impact on the incidence of cervical cancer in many countries. In developed countries, but not in any developing country although its use is widespread. The use of conventional cytology as the primary test method has been replaced by the use of liquid-based cytology in many countries that have organized cervical cancer screening programs, such as the United Kingdom, the Netherlands, and Denmark. The main advantages of using liquid-based cytology instead of primary conventional cytology are that it facilitates reflex testing (i.e., residual material can be tested for the presence of human papilloma virus if borderline/slightly dicariotic smears are present) and reduces the number of slides of unsatisfactory quality. This literature review study aims to further examine how conventional cytology compares to liquid-based cytology as a method used in conducting cervical cancer screening. The journal in this review literature uses 3 databases including Google Scholar, PubMed, and Science Direct using the keywords "liquid based cytology", "conventional cytology" and "cervical cancer screening". Literature searches are adjusted based on inclusion and exclusion criteria. The search results were obtained by 10 international journals. Results show that both conventional and liquid-based cytology are effective methods for cervical cancer screening. Although liquid-based cytology may have some advantages over conventional cytology, both methods have proven effective for detecting cervical pathologies.